2010
DOI: 10.1007/s11340-010-9353-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research on Failure Waves in Soda-Lime Glass

Abstract: A series of plate impact experiment with sodalime glass specimens in different thicknesses are conducted on a 57 mm diameter one-stage gas gun in order to further investigate the so-called failure wave phenomena under dynamic compressive loads. With the aid of the VISAR technique, the failure wave trajectory is explored, which shows that, apart from a constant failure wave velocity, an initial delay time for the failure wave to initiate at the impact surface of the specimen should be taken into consideration. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Brar et al, 3,4 Bless et al 5 and Bourne et al 6 further confirmed the existence of the failure wave in different glasses by manganin stress and strain gauges and high speed photography. This failure phenomenon has also been observed in polycrystalline ceramics, such as alumina, [7][8][9] silicon carbide 10 and boron carbide, 11 and other inhomogenous brittle materials, such as mortar 12 and 3D-C/SiC composites. 13 The previous experimental observation results reveal many properties of failure wave, which were reviewed by Bless and Brar 14 as follows.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Brar et al, 3,4 Bless et al 5 and Bourne et al 6 further confirmed the existence of the failure wave in different glasses by manganin stress and strain gauges and high speed photography. This failure phenomenon has also been observed in polycrystalline ceramics, such as alumina, [7][8][9] silicon carbide 10 and boron carbide, 11 and other inhomogenous brittle materials, such as mortar 12 and 3D-C/SiC composites. 13 The previous experimental observation results reveal many properties of failure wave, which were reviewed by Bless and Brar 14 as follows.…”
Section: Introductionmentioning
confidence: 74%
“…Over the last two decades, a lot of researches on the formation mechanism and propagation law of failure wave have been reported. 1,9,10,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] In addition, some theoretical models have been proposed to describe the various features of the failure wave phenomena. 9,25-29 However, there has not been a complete understanding of the failure wave, and some disagreement and controversy still exist between available data and theoretical predictions.…”
Section: Introductionmentioning
confidence: 99%